Persepsi Sistem Informasi Manajemen Proyek (SIMP) Berbasis Situsweb Terhadap Pelaksanaan Proyek (Studi Kasus : Pelaksanaan Proyek Konstruksi Simpang Tak Sebidang Pamulang di PT. Cinere Serpong Jaya) - Deddy Kiting; Moh. Azhar (Universitas Batanghari Jambi, 2023)
Success in the construction industry is related to the efficiency and effectiveness of project implementation. Construction projects are not only very complex, but also require project management in daily work in terms of efficiency and effectiveness. This study uses a study-survey type, the purpose of which is to examine and explain project management possibilities for the successful implementation of a project at STS-Pamulang. The statistical calculation used is the crosstab which tests whether there is a relationship between the lines consisting of: planning , controlling , organizing and directing the time, cost and quality of the project. The results of the study make it possible to conclude that, according to the respondents, the project management function influences the success of project implementation at STS-Pamulang. According to respondents, planning and control variables are two aspects that have a significant influence on the success of project implementation at STS-Pamulang. To achieve this success, stakeholders wish to reduce project duration/time by expanding the planning and organizational aspects of project management. If you want to reduce your overall costs, you need to improve the planning and management aspects. And finally, if we want to improve the quality of our projects, we need to improve the planning and management of project management.